EC market information for developing countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Trading conditions in the European market are changing rapidly and exporters from developing countries need to keep themselves informed of market opportunities and new legislation. The introduction of the Single European Market, the present Uruguay...